SISTEM MONITORING DAN EVALUASI PENERIMA PROGRAM KELUARGA HARAPAN (PKH) UNTUK KELUARGA PENERIMA MANFAAT (KPM) BERBASIS WEB di NAGARI KOTO TINGGI KECAMATAN ENAM LINGKUNG - Indra Warman; Selfen Asrizon (ITP Press, 2021)
The Effort to accelerate poverty reduction, the Government launched the Program Keluarga Harapan (PKH). This program aims to improve human quality by providing conditional cash assistance for poor families designated as Beneficiary Families in accessing health and education services, reducing the burden of spending, and increasing poor families' income. In implementing the Program Keluarga Harapan (PKH) it is necessary to monitor and evaluate the activities carried out on the beneficiary families in Nagari Koto Tinggi, Enam Lingkung District. This study aims to create an evaluation monitoring system for PKH beneficiaries. This evaluation monitoring system was built using the Laravel framework, PHP web programming, and DBMS MySQL, the output of a web-based information system for monitoring and evaluating PKH group data, categories, budget realization for Beneficiary Families, and graphic reports including Education, toddlers, pregnant women (health), persons with disabilities and the elderly (social welfare), the PKH evaluation monitoring system can assist PKH managers in monitoring the evaluation of Beneficiary Families data.